Income, Financial Literacy, and Financial Management Behavior - Peter Peter; Herlina Herlina; Amisiska Natalia Saragi (International Forum of Researchers and Lecturers, 2026)
Financial management plays a crucial role in individual financial planning, particularly in the context of increasingly unstable macroeconomic conditions. Effective financial management behavior enables individuals to allocate resources wisely, manage risks, and achieve financial sustainability in the long term. Therefore, identifying the key factors that influence financial management behavior is essential. This study aims to analyze the effect of income and financial literacy on financial management behavior (FMB). The population of this study consists of teachers and administrative employees aged 24 to 60 years from two educational institutions located in Bandar Lampung and Metro. Using a snowball sampling technique, a total of 93 respondents were obtained. Data were collected through an online survey questionnaire designed to measure income level, financial literacy, and financial management behavior. The collected data were then analyzed using a multiple regression model to test the proposed hypotheses. The results of the analysis indicate that both income and financial literacy have a positive and significant effect on financial management behavior. Individuals with higher income levels tend to demonstrate better financial management practices, while greater financial literacy enhances individuals’ ability to plan, control, and make informed financial decisions. These findings highlight the importance of improving financial literacy and income management skills to strengthen financial management behavior, particularly among educators and educational staff.